Cosmetic Appeal, HRQoL, and Effectiveness of Simple and Pseudotesticular Techniques of Orchidectomy in Prostate Cancer - Ijeoma N. C. Chibuzo; Augustine O. Takure; Olayiwola B. Shittu; Linus I. Okeke (Prostate Cancer)
Introduction. Orchidectomy is the most cost-effective means of hormonal therapy for locally advanced or metastatic prostate cancer (LAMP). However, cost-effectiveness should not detract from health-related quality of life (HRQoL) considerations. Bilateral simple orchidectomy (BSO) has been linked to negative psychometric deficits from an empty scrotum. This study compared the HRQoL, therapeutic efficacy, and cosmetic appeal of BSO with endogenous pseudotesticular techniques of bilateral subcapsular orchidectomy (BSCO) and bilateral-epididymal-sparing orchidectomy (BESO). Research Design. Nigerian patients with LAMP were randomised into three surgical arms: BSO, BSCO, and BESO. Expanded Prostate Cancer Index Composite-26 HRQoL and sociodemographic questionnaires were administered before and three months after orchidectomy. Serum testosterone and PSA were measured at 0, 1, 2, and 3 hours; 7 days; and 3 months postoperatively. Pseudotesticular volumes and cosmetic appeal were assessed at 3 months. Result. Sixty-three patients were recruited (24 BSO, 21 BSCO, 18 BESO), 73% of whom were low-income earners. There was no significant difference in the procedure cost nor the PSA or testosterone nadirs achieved over the three-month follow-up period (11.3, 12.6, 15.2 ng/ml (p=0.667) and 0.44, 0.64, 0.79 nmol/l (p=0.603) respectively). Those with pseudotesticles (BSCO, BESO) felt less emasculated (p=0.010). BSCO produced the least sexual bother, highest sexual function, and largest pseudotesticular volumes. The cosmetic appeal scores were similar between groups (77.9 ± 22.8, 81 ± 13.9, and 81.9 ± 22.5, respectively, p=0.858). Conclusion. Endogenous pseudotesticular techniques, when compared with BSO, reduce the negative psychological impact experienced by patients without increasing costs. BSCO produced the best pseudotesticular volumes and postoperative sexual function. This study is registered with the ClinicalTrials.gov of the National Institute of Health U.S. National Library of Medicine as TEPSO study, NCT03744494: Comparison of the Therapeutic Efficacy and Patient Satisfaction of Three Techniques of Bilateral Orchidectomy in Prostate Cancer Patients of a Nigerian Sub-population. Registration completed on 16th of November, 2018 (registered retrospectively) NCT03744494.